Physiological response to water immersion: a method for sport recovery? - Wilcock, I. M.; Cronin, J. B.; Hing, W. (Sports Medicine, 2006)
Recovery from exercise can be an important factor in performance during repeated bouts of exercise. In a tournament situation, where athletes may compete numerous times over a few days, enhancing recovery may provide a competitive advantage. One method that is gaining popularity as a means to enhance post-game or post-training recovery is immersion in water. Much of the literature on the ability of water immersion as a means to improve athletic recovery appears to be based on anecdotal information, with limited research on actual performance change. Water immersion may cause physiological changes within the body that could improve recovery from exercise. These physiological changes include intracellular-intravascular fluid shifts, reduction of muscle oedema and increased cardiac output (without increasing energy expenditure), which increases blood flow and possible nutrient and waste transportation through the body. Also, there may be a psychological benefit to athletes with a reduced cessation of fatigue during immersion. Water temperature alters the physiological response to immersion and cool to thermoneutral temperatures may provide the best range for recovery. Further performance-orientated research is required to determine whether water immersion is beneficial to athletes.